Características epidemiológicas das fraturas intertrocantéri cas do fêmur proximal atendidos no Hospital Municipal Albert Schweitzer – RJ - Rugel Rivera, Miguel Angel (2020)
Intertrochanteric fractures are defined as extracapsular fractures of the proximal femur that occur between the greater and the lesser trochanter; are frequent in the elderly, considered a devastating consequence of osteoporosis, affect more women, are commonly associated with low-energy trauma and, although present few complications related to consolidation, are related to functional deficits, high rates of morbidity and mortality, in addition to high costs to health services. They represent an important public health problem worldwide due to their high incidence. This is a retrospective study based on a survey of medical records, aiming to characterize patients with intertrochanteric fractures of the proximal femur treated at the Albert Schweitzer Municipal Hospital - RJ from January 2017 to December 2019. In this study, 603 were analyzed medical records with pre-dominance in the female population, with 466 cases (77.3%) and 137 cases (22.7%) in the male population; in relation to the age variable, the greatest presence was found in the range of 71 to 80 years, as well as from 81 to 90 years, representing 32.5% (196 patients) and 39.6% (239 patients); in the trauma mechanism variable, 96.4% (581 patients) had low-energy trauma and 3.6% (22 patients) had high-energy trauma; in the variable affected side, 47.8% (288 patients) had a fracture on the right side, and 52.2% (315 patients) had a fracture on the left side; in the variable social status, 8.8% (53 patients) had the social status "Alone", and 91.2% (550 patients) had the social status "With the Family"; in the variable associated diseases, a higher frequency was observed in diseases of the cardiovascular system, representing 45.9% (277 patients). The justification for this study is to specify the characteristics of this injury, in addition to helping to select preventive strategies and actions for the development of a health policy that aims to reduce the incidence of this type of injury.